Simulation and performance of BPSK and 8-PSK in CDMA by using cyclic codes for digital communication system / Mohd Fazri Abd Latif - Abd Latif, Mohd Fazri (2008)
This project illustrates the simulation and performance of BPSK and 8-PSK in CDMA. This model consists of transmission channel, transmitter and receiver. This simulation is deal with two channels, channel one is using BPSK and channel two is using 8-PSK. Cyclic codes is use to encode and decode the digital signal of the two channels before modulation and after demodulation process. The main objective is to compare and identify which channel is better by analyzing the performance of both channels. Besides, this project will show why CDMA is the most excellent multiple access compare to other. This project is simulated via Matlab Version 7.5.